(untitled) (European Journal of Behavioral Sciences, 2018)
The purpose of this study was to investigate the relationship between the role of teacher and the motivation of students’ research. The method of this research was the correlation and the statistical population of this study was all students of martyr Ayatollah Sadeghib during the academic year of 97-96. A randomized sampling method was used to collect information and data from a research motivation questionnaire. In this research, the bivariate correlation analysis method was used to analyze the data. Findings showed that the role of teacher with the motivation of student research is meaningful and the teacher can increase student motivation.